Enhancing Students' Scientific Argumentation Skills through STEM-Based Problem Based Learning - Muspiroh, Novianti; Shofiyah, Shofiyah; Nada, Shofwatun; Kusmawan, Udan (International Journal of Research in STEM Education, 2024)
This study examines the efficacy of STEM-based Problem Based Learning (PBL) in enhancing scientific argumentation skills among students, focusing on respiratory system material. Employing a Quasi-Experimental Design, this research involved tests, observations, and questionnaires to assess the changes in students' scientific argumentation abilities. The study enrolled students from two classes, utilizing a purposive sampling technique to ensure comparability. Results indicated a significant improvement in students' scientific argumentation skills, with average scores increasing from 81.57% in the first meeting to 86.14% in the second meeting, categorized as very good. Additionally, statistical analysis revealed a notable difference between the experimental and control groups, with a p-value less than 0.05, confirming the effectiveness of the STEM-based PBL approach. The study suggests that integrating STEM into PBL can significantly enhance students' critical thinking and problem-solving skills, recommending wider application in educational settings to better prepare students for complex scientific challenges.